PERANAN HOME INDUSTRY DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Agung Wahyu Subasriyanto; Fauzy Ridwan, Irwan (LPPM IAIT, 2024)
The purpose of this research is to determine the role of home businesses that produce traditional food in Cihaur Manonjaya Village, to determine the supporting and inhibiting factors in home businesses and their role in improving the economy of the Cihaur Manonjaya community, Tasikmalaya district, as well as an Islamic Economic review of Home Businesses in Cihaur Manonjaya Village . The data analysis method is descriptive qualitative, namely explaining in depth and then conducting qualitative analysis which is described in the form of a description. Research findings regarding the production process of home businesses that produce food in Cihaur Manonjaya are managed simply and do not meet the standards set by the government. Supporting factors in this business are people's high buying interest and ease of marketing, the skills and knowledge that home entrepreneurs have in producing their products, people's desire to increase their income, and the capital that home industry entrepreneurs have. Meanwhile, the inhibiting factor is that the products they produce are easily damaged and do not last long. Even though there are inhibiting factors, this business has contributed to improving the economy of the Cihaur Manonjaya community